1995
DOI: 10.1007/bf00031995
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity on the life history and fitness of Daphnia magna: variability within and between populations

Abstract: The life history traits of Daphnia magna were studied in laboratory experiments under freshwater and brackish (5%o salinity) conditions . The variability of responses within and between populations was examined by comparing 11 clones from a brackish lake and 10 clones from a freshwater pond . Experimental clones were hatched from ephippia collected from the sediment and thus represent random samples of the clone banks of each population .Most clones with a high salinity tolerance were from the population of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 9 publications
7
29
0
Order By: Relevance
“…Many studies have shown that locally acting selective forces (particularly predation) lead to the formation of local races or "ecotypes" (local adaptation, see Weider and Hebert, 1987;De Meester, 1996a, 1996bBoersma et al, 1999;Cousyn et al, 2001;De Meester et al, 2002). This has also been reported in Daphnia populations from brackish vs. freshwater environments (Weider and Hebert, 1987;Teschner, 1995;Barry et al, 2005).…”
Section: Introductionmentioning
confidence: 88%
“…Many studies have shown that locally acting selective forces (particularly predation) lead to the formation of local races or "ecotypes" (local adaptation, see Weider and Hebert, 1987;De Meester, 1996a, 1996bBoersma et al, 1999;Cousyn et al, 2001;De Meester et al, 2002). This has also been reported in Daphnia populations from brackish vs. freshwater environments (Weider and Hebert, 1987;Teschner, 1995;Barry et al, 2005).…”
Section: Introductionmentioning
confidence: 88%
“…Additionally, growth rate of both daphnid species was also negatively affected and maturation was delayed at the highest concentrations. Similarly, Teschner (1995) concluded that clones of D. magna under brackish conditions grew more slowly and matured on average later than under freshwater conditions. Nevertheless, our results demonstrated that D. magna reproduces and lives well at salinity concentrations below 4.55 g.L -1 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies (Barron et al 2002) proved phytoplankton can adapt to salinity conditions, although this process becomes slower as NaCl concentration increases. Some algae (such as the ones belonging to the genus Dunaliella) are haloterant, growing at high saline media due to physiological adaptations, such as glycerol intracellular accumulation (Avron 1986) and a salt-induced protein (p60) present in the plasma membrane (Fisher (Teschner 1995, Schallenberg et al 2003, Rokneddine & Chentoufi 2004.…”
Section: Discussionmentioning
confidence: 99%
“…The German clones were collected from the Großer Binnensee, a shallow slightly brackish and hypertrophic coastal lake, which contains unknown densities of mainly bream, roach, and perch (Lampert 1993), and from the Rixdorfer Pferdetränke, a small eutrophic fishless pond. These clones were used previously in life-table experiments involving different levels of salinity (Teschner 1995) and fish kairomones (Teschner unpubl. data).…”
Section: Methodsmentioning
confidence: 99%